Knowledge of Oral Health Among the People of Rural Nepal (Cases from Lalitpur District) - Sakha, Amit Kumar; Menariya, S. L. (Nepal Journal of Multidisciplinary Research, 2021)
Good oral health is the condition of free of illnesses that empowers to perform ordinary capacities. It is accounted for that there is a cozy connection between oral illnesses and other foundational diseases like diabetes, digestive disease, stroke, cardiovascular disease, metabolic syndrome, adverse pregnancy outcomes, obesity, et al. So, it is important to maintain good oral health and one must have knowledge of oral health and how to maintain dental and oral hygiene. The main objective of this study is to identify the knowledge of oral health among 35 to 45-year people of Rural Nepal. the study had adopted the mixed design (method) – both quantitative and qualitative tools were used to collect the data. It was a cross-sectional study. The study was conducted in four Rural Municipalities of Lalitpur district: Gotikhel, Chaughare, Malta and Bhardah. The data was collected from 369 respondents by using the structured survey questionnaire. The majority of people (68%) reported that they had heard of oral disease. Though, still, 32% had no knowledge of oral health. There was a significant association between the literate and illiterate on the basis of hearing about the oral disease because of p =.000 which is lesser than .05 significant level. Radio and Television were the main source of getting knowledge of oral health. All the household may not have equal access on the Radio and Television program so there was a need to organize the awareness campaign in rural society to aware the people.